2009
DOI: 10.3844/ajptsp.2009.130.135
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicology of Tartrazine (FD and C Yellow No. 5) in Swiss Albino Mice

Abstract: Abstract. Problem statement: Tartrazine (FD and C Yellow No. 5) is an orange-colored widely used in food products, drugs and cosmetics. This color has a potential toxicological risk. The current study evaluated the effect of sub-chronic consumption of tartrazine on the male reproductive system. Approach: Tartrazine was administered to adult male mice in drinking water at doses of 0, 0.1, 1 and 2.5% for 13 weeks. After that period, the weights of testes, epididymides and seminal vesicles were determined. Sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 24 publications
6
33
1
3
Order By: Relevance
“…These results are similar to the observations of Peiris et al (1995) in rats treated with methamidophos and of Mehedi et al (2009) in Swiss albinos mice treated with tartrazine. This decrease in feed consumption could be due to the decrease in metabolism, or inhibition of the hunger resulting in a lack of appetite or anorexia.…”
Section: Discussionsupporting
confidence: 82%
“…These results are similar to the observations of Peiris et al (1995) in rats treated with methamidophos and of Mehedi et al (2009) in Swiss albinos mice treated with tartrazine. This decrease in feed consumption could be due to the decrease in metabolism, or inhibition of the hunger resulting in a lack of appetite or anorexia.…”
Section: Discussionsupporting
confidence: 82%
“…The lumens of seminiferous tubules were also found to be reduced, indicating their compressed and bundled disorientation, whereas the same were radially oriented in control testes. Similarly, Mehedi et al (2009) [38] demonstrated the histological damages in the seminiferous tubules and Leydig cells of tartrazine-treated mice. So, the altered architecture of seminiferous tubules in tartrazine group of animals is very well correlated to the damaged membrane proteins and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Mehedi et al (2009) reported that tartrazine has toxic effects on the reproductive organs comprising, decrease in reproductive performance, reduced sperm count and increased rate of sperm anomalies in mice with doses of 0, 0.1, 1.0 and 2.5% for 13 weeks.…”
Section: Reproductive and Developmental Toxicity Of Tartrazinementioning
confidence: 99%